Unraveling MoS2 and Transition Metal Dichalcogenides as Functional Zinc‐Ion Battery Cathode: A Perspective. Issue 1 (3rd November 2020) - Lee, Wee Siang Vincent; Xiong, Ting; Wang, Xiaopeng; Xue, Junmin
Abstract: The zinc‐ion battery (ZIB) is considered as one of the most important alternative battery chemistries to date. However, one of the challenges in ZIB development is the limited selection of materials that can exhibit satisfactory Zn 2+  storage. Transition metal dichalcogenides (TMDs) are widely investigated in energy‐related applications due to their distinct physical and chemical properties. In particular, the wide interlayer spacings for these TMDs are particularly attractive as viable Zn 2+  storage sites. Despite the suitability of TMDs in ZIB application, they are still not widely explored due to their limited report in this area. In this perspective review, the key challenge of TMDs, especially for MoS2, in their utilization as ZIB cathode are discussed. The various reports on MoS2  and TMDs as ZIB cathodes are also summarized. In order to elicit reasonable Zn 2+  storage ability in MoS2  and TMDs, four key modification strategies are proposed: 1) interlayer engineering, 2) defect engineering, 3) hybridization, and 4) phase engineering. These proposed modification strategies may be able to address the challenge of inadequate Zn 2+  storage in MoS2  and TMDs. Finally, this review ends with a conclusion and outlook of MoS2  and TMDs in the future development of ZIB cathodes. Abstract : Transition metal dichalcogenides (TMDs) are attractive as zinc‐ion battery cathode due to their distinct physical and chemical properties. Despite the suitability of TMDs in ZIB applications, they are not widely explored. In this perspective review, key challenge of TMDs, especially for MoS2, as ZIB cathodes and proposed strategies to elicit reasonable Zn 2+  storage performance are discussed.